GBKP Kuta Jurung: Jejak Masuknya Missionaris pada Masyarakat Karo di Kabupaten Deli Serdang - Defri Elias Simatupang (Berkala Arkeologi Sangkhakala, 2006)
AbstractGBKP Kuta Jurung is a protestant church for Batak Karo community in Kuta Jurung, Deli Serdang - Norh Sumatera. In Agust 2006, Balar Medan have found a christian old grave in there who have guessed that a missionary buried in it. This is a new data that will needed in the future for investigation more complete about the history of missionaries who had done their service for Karonese since 19th century.